2017
DOI: 10.20524/aog.2017.0220
|View full text |Cite
|
Sign up to set email alerts
|

" Surgical options for full-thickness rectal prolapse: current status and institutional choice"

Abstract: Full-thickness rectal prolapse (FTRP) is generally believed to result from a sliding hernia through a pelvic fascial defect, or from rectal intussusception. The currently accepted cause is a pelvic floor disorder. Surgery is the only definitive treatment, although the ideal therapeutic option for FTRP has not been determined. Auffret reported the first FTRP surgery using a perineal approach in 1882, and rectopexy using conventional laparotomy was first described by Sudeck in 1922. Laparoscopy was first used by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 73 publications
(128 reference statements)
2
18
1
Order By: Relevance
“…The Altemeier procedure is considered an appropriate surgical procedure with favorable outcomes; however, different postoperative complications and recurrence rates have been reported for this procedure in the presence or absence of levatorplasty. 13,14 In the present study, we compared the pre-and postoperative scores of patients using the Wexner scale, and the results showed that the score did not change in 50% of the cases. The mean preoperative score was similar between the groups, which indicated that they were comparable; however, the results of the statistical analyses showed that neither the difference in the pre-and postoperative scores nor the absolute postoperative scores were significantly different between the two groups.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The Altemeier procedure is considered an appropriate surgical procedure with favorable outcomes; however, different postoperative complications and recurrence rates have been reported for this procedure in the presence or absence of levatorplasty. 13,14 In the present study, we compared the pre-and postoperative scores of patients using the Wexner scale, and the results showed that the score did not change in 50% of the cases. The mean preoperative score was similar between the groups, which indicated that they were comparable; however, the results of the statistical analyses showed that neither the difference in the pre-and postoperative scores nor the absolute postoperative scores were significantly different between the two groups.…”
Section: Discussionmentioning
confidence: 78%
“…Therefore, the sphincter muscle can be contracted appropriately and the its function can improve over time. 10 However, there are few reports [11][12][13][14][15] available about the effect of the Altemeier procedure on the continence status of the patients. There is controversy involving adult fecal incontinence after the Altemeier procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Our patients are elderly with limited physiological reserve in two vital organs, heart and lungs, so the recommended procedure is transperineally, but another problem to be considered is the high recurrence rate. Anal encirclement using wire has been performed often but has a higher morbidity and recurrence rate [14]. To overcome these challenges, we developed a modified operating technique.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, laparoscopic techniques have been added as treatment options for RP because of their advantages of early recovery, less pain, and the possibility of lower morbidity. Some researchers have reported that laparoscopic procedures represent a new surgical approach as an alternative to conventional abdominal procedures [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%